Identification Of Nbs-Lrr Genes In The Genome And Qtl Regions Of Chickpea (Journal of Plant Disease Sciences, 2019)
Chickpea is one of the most important legume crops of interest all over the world. A variety of biotic and a biotic stresses form the major production constraint in chickpea. Among biotic stresses, Fusarium wilt of chickpea is one of the most devastating diseases of chickpea. The present study elucidates the molecular basis of wilt disease resistance in chickpea. Here the genome wide identification of NBS LRR containing genes was performed. Of the 91 genes, we could develop 36 SSR markers referred to as RSSRs (resistance gene based SSRs). The SSRs were validated on a set of 12 chickpea genotypes to demonstrate their further use in trait mapping and gene discovery studies. The wilt
Keywords: A biotic and biotic stresses; Fusarium wilt; Genome annotation; NBS LRR genes; RSSRs